Values Education in Primary School 4th Grade Social Studies Course: An Action Research - Ethem Gürhan (MANDAILING GLOBAL EDUKASIA, 2026)
Values education plays a critical role in fostering students’ moral, social, and civic development, particularly during the primary school years when foundational attitudes and behaviors are formed. Within this context, Social Studies courses offer a key pedagogical space for integrating values education into everyday classroom practices. The purpose of this study is to examine how values education practices implemented through an action research framework influence students’ understanding of values, classroom interactions, and observable behaviors in a fourth-grade Social Studies classroom. The study adopted a qualitative action research design and was conducted with 26 fourth-grade students and one classroom teacher in a public primary school in Türkiye. Data were collected over a eight-week implementation period through classroom observations, reflective teacher journals, semi-structured student interviews, and student-produced materials. The values education program focused on core values including respect, responsibility, empathy, justice, helpfulness, and tolerance, and was implemented using student-centered and experiential learning activities aligned with the Social Studies curriculum. The collected data were analyzed using thematic analysis, with inter-coder reliability ensured through independent coding procedures. The findings indicate that values education practices contributed to students’ conceptual understanding of values, promoted more respectful and cooperative classroom interactions, and supported the reflection of value-based behaviors in daily classroom routines. The results further suggest that sustained and experiential values education practices can positively influence classroom climate by fostering inclusivity, empathy, and shared responsibility among students. Additionally, the action research process enhanced teacher reflexivity by enabling continuous reflection and adaptation of instructional practices in response to classroom dynamics. Overall, this study demonstrates that values education, when embedded within classroom life through action research, can function as a transformative pedagogical process rather than a set of isolated instructional outcomes. The findings highlight the potential of action research to support both student development and teacher professional growth, offering practical insights for educators seeking to integrate values education into primary school Social Studies instruction.